Control of Sclerotium cepivorum and growth promotion in garlic (Allium sativum) whit antagonist microorganisms - Zapata-Narváez, Yimmy Alexander; Gómez-Marroquín, Magda Rocio (Agronomía Mesoamericana, 2022)
Introduction. White rot produced by Sclerotium cepivorum causes losses greater than 50 % in garlic crops, the main control alternative is the application of chemical fungicides with limited efficacy, it is necessary to integrate alternatives that contribute to the development of disease management strategies. Objective. To evaluate the efficacy of antagonistic microorganisms applied individually and as a mixture against S. cepivorum in garlic. Materials and methods. This research was carried out under controlled conditions at the Corporacion Colombiana de Investigacion Agropecuaria (AGROSAVIA), during 2019. The soil was artificially infested with sclerotia (10 sclerotia/g soil). The efficacy of the individual use and in mixtures under different drench applications frequencies of three antagonists Trichoderma koningiopsis, Trichoderma asperellum, and Bacillus amyloliquefaciens, strains Th003, Th034, and Bs006, respectively, in the control of S. cepivorum in garlic and in the promotion of plant growth expressed as root, bulb, and foliar dry weight was evaluated. Results. The highest efficacy, with 65 % in disease control was obtained when applying Th003 at sowing and 15 das and with 56 % when applying the mixtures of Th003 + Th034 at sowing, Th003 + Th034 at sowing, 15, 30, and 45 das, and Th003 + Bs006 at sowing, 15 and 30 das, while Tebuconazole presented an efficacy of 35 %. Conclusion. The application of antagonists individually or in mixtures at different frequencies reduced mortality due to white rot in garlic. A positive effect on garlic plants growth was observed with the application of Th003 + Bs006 strains at sowing, 15 and 30 das, Th003 at sowing, Th003 at sowing and 15 dad, and Th034 + Bs006 at sowing, with higher values of dry weight with respect to the control.